2012
DOI: 10.1212/wnl.0b013e3182698cd8
|View full text |Cite
|
Sign up to set email alerts
|

Extreme delta brush

Abstract: Extreme delta brush is a novel EEG finding seen in many patients with anti-NMDAR encephalitis. The presence of this pattern is associated with a more prolonged illness. Although the specificity of this pattern is unclear, its presence should raise consideration of this syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
469
3
40

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 648 publications
(533 citation statements)
references
References 11 publications
21
469
3
40
Order By: Relevance
“…The authors described a rhythmic delta activity 1-3 Hz with superimposed bursts of rhythmic 20-30 Hz beta frequency activity "riding" on each delta wave. The name extreme delta brush applies because of its resemblance to the waveforms seen in premature babies [7].…”
Section: Discussionmentioning
confidence: 99%
“…The authors described a rhythmic delta activity 1-3 Hz with superimposed bursts of rhythmic 20-30 Hz beta frequency activity "riding" on each delta wave. The name extreme delta brush applies because of its resemblance to the waveforms seen in premature babies [7].…”
Section: Discussionmentioning
confidence: 99%
“…Brain MRI is often normal. EEG changes in the form of extreme delta brushes have been described in comatose patients, suggestive of prolonged clinical course [4]. Relation to ovarian teratoma in females demand a thorough evaluation for occult tumors.…”
Section: Editorialmentioning
confidence: 99%
“…Numerous case reports, case series, cohort studies, randomized placebo controlled studies have reported a wide range of response (no response to significant response) [4][5][6][7][8][9]. Beware of small sample size for these studies.…”
Section: Editorialmentioning
confidence: 99%
“…The common pattern is slowing which may be diffuse or focal 8,10,12,18 . A recent study identified a unique EEG pattern, called "extreme delta brush" which is beta-delta complexes, in adults with anti-NMDAR encephalitis 24 . Epileptiform activity is less common than slowing 10,18 , but may include electrographic seizures in approximately 60% when continuous monitoring is undertaken 10 .…”
Section: Electroencephalogram (Eeg)mentioning
confidence: 99%
“…Changes restricted to the temporal lobe or limbic system, are the commonest findings in patients with limbic encephalitis. Abnormalities reported with more diffuse encephalitis have been in the periventricular white matter, limbic or temporal lobes 9,18,24,25 , brainstem, basal ganglia and cerebellum 12,23 . Meningeal enhancement has also been found occasionally 28 .…”
Section: Imagingmentioning
confidence: 99%